Avaliação tecnológica e clínica de protetores nasais empregados na ventilação não invasiva de recém-nascidos - Camillo, Débora de Fátima (2016)
The nasal injury resulting from the use of non-invasive ventilation (NIV) is an adverse event increasingly common in the newborn intensive care unit (NICU) and shows the short and long term consequences. This lesion can result both aesthetic and functional sequelae, limit the use of NIV in newborns who need this ventilatory support, cause discomfort and septicemia, may thereby increase the length of stay in NICU. This research aims to evaluate technological and clinically nasal protectors used with NIV of newborns admitted to the NICU. The methodology consisted primarily in raising the possible causes of nasal injury and assess the risk factors associated with its development. Then, it was conducted a randomized clinical trial to compare the effects of three kind of nasal protector and new and sterilized prongs on the severity of nasal lesions. And finally, it was performed the thermal and structural characterization of nasal protection after being aged with temperature and humidity inside the neonatal incubator. The main causes of injury were related to characteristics of the material, equipment problems, assistive, neonatal and professional factors. In this study, it was found as risk factors: gestational age, weight at birth, the total time stay in the NIV, the reuse of this support, the time of first use and reuse of NIV and the length of stay in the NICU. They were not observed significant differences in lesion severity when compared the three protectors studied, nor when used new and sterilized prongs. The materials analysis indicated that exposure to temperature and humidity changed the percentage of crystallinity and the roughness of the nasal protections studied.